Impact of reduced group size on patient adherence and functional outcomes in cardiac rehabilitation: insights from a COVID-19 pandemic natural experiment - Chait, Rachael M.; Ossi, Julia; Colbert, Brett M.; Huang, Eric; Gilchrist, Juliann; Garcia, Thais; Andrade-Bucknor, Sharon; Seixas, Azizi (Frontiers in Rehabilitation Sciences, 2024)
IntroductionCardiac rehabilitation (CR) adherence and functional outcomes were measured after COVID-19 regulations reduced group sizes to one-on-one, modeling a natural experiment.MethodsA retrospective analysis using a natural experiment model measured participants in 12 weeks of CR during the 17 months before and after a COVID-19-related closure was conducted. The age, sex, race, ethnicity, and referral diagnoses of the pre-COVID-19 closure and post-COVID-19 closure groups were analyzed using a student's unpaired T-test. Adherence (completion rate of CR) and functional outcomes [change in six-minute walk test (6MWT)] were assessed between the two groups using unpaired two-tailed student T tests in GraphPad Prism and confidence intervals were calculated with the Baptista-Pike method.ResultsThere were 204 patients in the pre-COVID-19 group and 51 patients in the post-COVID-19 group, due to the smaller group sizes in the post-COVID-19 group, with no significant differences in baseline characteristics between the groups. The pre-COVID-19 group had a higher patient-to-provider ratio [2.8 patients/provider (SD 0.74)] relative to the post-COVID-19 group [0.4 patients/provider (SD 0.12); p < 0.0001]. The post-COVID-19 group had a higher completion rate than pre-COVID-19 group [75% vs. 21%; OR 10.9 (95% CI, 5.3–21.3, p < 0.0001)]. Among those that completed CR, there was no significant difference between groups in 6MWT improvement [+377.9 ft. (n = 47; SD 275.67 ft.) vs. +346.9 ft. (n = 38; SD 196.27 ft.); p = 0.59].DiscussionThe reduction in group size to one-on-one was associated with 10 times higher odds of CR completion. Among those that completed CR, functional outcomes were not influenced by group size. Thus, pursuit of one-on-one sessions may improve CR adherence.